Potential Involvement of Osteopontin in Inflammatory and Fibrotic Processes in Pulmonary Embolism and Chronic Thromboembolic Pulmonary Hypertension - Kölmel, Sebastian; Hobohm, Lukas; Käberich, Anja; Krieg, Valentin J.; Bochenek, Magdalena L.; Wenzel, Philip; Wiedenroth, Christoph B.; Liebetrau, Christoph; Hasenfuß, Gerd; Mayer, Eckhard; Konstantinides, Stavros V.; Schäfer, Katrin; Guth, Stefan; Lankeit, Mareike (Thrombosis and Haemostasis, 2019)
Background Inflammation and incomplete thrombus resolution leading to obstructive fibrotic remodelling are considered critical mechanisms for the development of chronic thromboembolic pulmonary hypertension (CTEPH) after pulmonary embolism (PE). Osteopontin (OPN) is involved in a variety of biological processes including inflammation and tissue fibrosis.Methods OPN plasma concentrations were measured in 70 CTEPH and 119 PE patients. Tissue material from 6 CTEPH patients removed during pulmonary endarterectomy and murine venous thrombi induced by subtotal ligation of the inferior vena cava in C57BL/6 mice were analysed by (immuno)histochemistry.Results CTEPH patients had higher OPN plasma concentrations (median, 106.9 [interquartile range, 75.6–155.9]) compared to PE patients (90.4 [53.3–123.9] ng/mL, p = 0.001). OPN- and matrix metalloproteinase (MMP)-9-positive cells were predominantly present in myofibroblast-rich and profibrotic areas of CTEPH tissue material. Early stages of murine thrombus resolution were characterised by high numbers of OPN- and MMP-2-positive cells while OPN was almost absent in fresh thrombi of CTEPH tissue material. PE patients with OPN plasma concentrations of < 55 ng/mL had a 15.2-fold (95% confidence interval, 1.7–135.5, p = 0.015) increased risk for a diagnosis of CTEPH during follow-up.Conclusion The results of the present observational translational study point to a possible involvement of OPN in the pathogenesis of CTEPH by affecting early inflammatory and late fibrotic processes.
Keywords: thrombus resolution; fibrosis; inflammation; osteopontin; chronic thromboembolic pulmonary hypertension